A Universal Additive Strategy to Reshape Electrolyte Solvation Structure toward Reversible Zn Storage (Adv. Energy Mater. 15/2022). Issue 15 (21st April 2022) - Li, Tian Chen; Lim, YewVon; Li, Xue Liang; Luo, Songzhu; Lin, Congjian; Fang, Daliang; Xia, Sunwen; Wang, Ye; Yang, Hui Ying
Abstract : Solvation Structure Regulation In article number 2103231, Hui Ying Yang and co‐workers focus on a universal strategy to reshape zinc solvation structures via introducing carbonyl‐containing polar organic solvents. The NMP molecule is shown in the image as the key element. The background is an ocean, which corresponds to the aqueous environment. The yellow spheres represent zinc cations. The laser between zinc ion and carbonyl oxygen from the NMP molecule indicates the interaction between them, leading to reorganized solvation structure.